ETHODOLOGICAL PRINCIPLES OF STRUCTURAL AND MORPHOMETRIC ANALYZES OF MOUNTAIN RELIEVE (CASE STUDY FROM CARPATHIAN MODELING POLYGON) - Andriets, T. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Consideration is given to the structure-morphometric analysis base principles for the latest tectogenesis studying. The possibility of classic technique application for mountain regions in using GIS-technologies (Spatial Analysis and Spatial Modeling) has been shown. Initial stages determination morphometric relief indexes by example the Ukrainian Carpathians have been carried out. Basic surfaces analysis is permitted to observe local tectonic structures in relief and their configuration on difference hypsometric levels.